Determination of the Optimal Level of Dietary Zinc for Newly Weaned Pigs: A Dose-Response Study - Sally V. Hansen; Natalja P. Nørskov; Jan V. Nørgaard; Tofuko A. Woyengo; Hanne D. Poulsen; Tina S. Nielsen (Animals, 2022)
One hundred and eighty individually housed piglets with an initial body weight of 7.63 ± 0.98 kg (at 28 days of age) were fed a diet containing either 153, 493, 1022, 1601, 2052 or 2407 mg zinc/kg (added Zn as zinc oxide; ZnO) from day 0–21 post weaning to determine the optimal level of Zn for weaned piglets. Body weight, feed intake and faecal scores were recorded, and blood and faecal samples were collected. Dietary Zn content quadratically affected both feed intake and gain in the first two weeks, with an approximately 1400 mg Zn/kg diet and a Zn intake of 400 mg/day as the optimal levels. The relative risk of diarrhoea increased up to 60% at day 7 and 14 if serum Zn status dropped below the weaning level (767 µg/L), and maintain the weaning serum Zn status required approximately 1100 mg Zn/kg (166 mg Zn/day) during week 1. Blood markers of intestinal integrity (D-lactate and diamine oxidase) were unaffected by dietary Zn, and dietary Zn levels of 1022 and 1601 mg/kg did not affect the faecal numbers of total bacteria, Lactobacilli and E. Coli bacteria compared to 153 mg Zn/kg. These results indicate that the requirement for Zn in newly weaned piglets may be substantially higher than currently assumed.